2022
DOI: 10.1093/ej/ueac078
|View full text |Cite
|
Sign up to set email alerts
|

The Long-Term Effects of Student Absence: Evidence from Sweden

Abstract: Despite the relatively uncontested importance of promoting school attendance in the policy arena, little evidence exists on the causal effect of school absence on long-run outcomes. We address this question by combining historical and administrative records for cohorts of Swedish individuals born in the 1930s. We find that elementary school absence significantly reduces contemporaneous academic performance, final educational attainment and labor income throughout the life-cycle. The findings are consistent wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 40 publications
2
21
0
Order By: Relevance
“…They also align with US studies indicating negative consequences of absences on educational and civic participation (Ansari et al, 2020;Liu et al, 2021). Our findings regarding the consequences of school absences on final educational attainment are also consistent with those of Cattan et al, (2022) for the Swedish context, which is the only other study examining long-term effects of school absences on educational and labour market outcomes in mid-adulthood. Despite the fact that absences have the expected negative effect on all labour market outcomes in both studies, we found statistically significant effects on nonemployment but not earnings, whereas Cattan et al (2022) found the opposite pattern.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…They also align with US studies indicating negative consequences of absences on educational and civic participation (Ansari et al, 2020;Liu et al, 2021). Our findings regarding the consequences of school absences on final educational attainment are also consistent with those of Cattan et al, (2022) for the Swedish context, which is the only other study examining long-term effects of school absences on educational and labour market outcomes in mid-adulthood. Despite the fact that absences have the expected negative effect on all labour market outcomes in both studies, we found statistically significant effects on nonemployment but not earnings, whereas Cattan et al (2022) found the opposite pattern.…”
Section: Discussionsupporting
confidence: 90%
“…Hibbett et al (1990) looked at Great Britain and found that skipping school at age 16 was linked to lower-paying jobs, less stable career paths, and more unemployment at age 23. Only Cattan et al (2022) used Swedish register and school administrative data to look at the long-term effects of primary school absences on employment and earnings up to the age of 40. They found that absences in early childhood reduced cohort member's final educational attainment and labour income but were not significantly related to employment.…”
Section: Consequences Of School Absenteeismmentioning
confidence: 99%
See 3 more Smart Citations